The Effect of Political and Economic Factors on Corporate Tax Rates - Åsa Hansson; Susan Porter; Susan Perry Williams (Research Institute of Industrial Economics (IFN), 2012)
Economists and political scientists have long been interested in factors that affect the statutory tax rate on businesses set by federal governments. In this study, we examine the impact of political and economic factors on several measures of tax rates and tax incentives offered across 19 developed countries for the years 1979 through 2005. Our results indicate that while economic conditions such as openness, strategic interaction, budget constraints, economic downturns and an aging population all influence the rate of tax set by governments, the political structure of the federal government has a significant impact in the form of economic stimulus given. Importantly, our results suggest that different economic and political structures affect the level of incentives offered beyond those factors that affect the level of tax rates. These results are relevant to the current tax debate facing many governments as they consider implementing new policies to attract foreign direct investment and retain and grow domestic business. The impact of the political structure on the ability to enact legislation is significant after controlling for economic factors. This indicates that as the marketplace continues to become more international, it will become increasingly important for governments to find opportunities to work within their systems to enact legislation that enables their business community to compete internationally.
Keywords: D72; H25; H73; 330; Corporate tax rates; Tax competition; Political structure